PENGARUH TENUR KAP, REPUTASI KAP, SPESIALISASI INDUSTRI KAP DAN ROTASI KAP TERHADAP KUALITAS AUDIT (Studi Pada Perusahaan Manufaktur di BEI Periode 2005-2010) - Ispudyastari Selvi Mahetmi (AKT 12 UMY 309, 2012)

(untitled)
This paper is trying to examine the effect of KAP tenure, KAP reputation, KAP industry specialization and KAP rotation to quality audit. The object of this study is a manufacturing company listed on the Stock Exchange 2005-2010 period. This study uses data collection techniques that is purposive sampling. The population of this study were 450 companies. And proxy which used in this study to measure the quality of the audit was discretionary accruals. The results of statistical tests indicat